Tweeting links to Cochrane Schizophrenia Group reviews: a randomised controlled trial - Adams, Clive E.; Jayaram, M.; Bodart, A.Y.M.; Sampson, S.; Zhao, S.; Montgomery, A.A. (BMJ Publishing Group Ltd, 2016)
Objective: To assess the effects of using health social media on web activity. Design: Individually randomised controlled parallel group superiority trial. Setting: Twitter and Weibo. Participants: 170 Cochrane Schizophrenia Group full reviews with an abstract and plain language summary web page. Interventions: Three randomly ordered slightly different 140 character or less messages, each containing a short URL to the freely accessible summary page sent on specific times on one single day. This was compared with no messaging. Outcome: The primary outcome was web page visits at 1 week. Secondary outcomes were other metrics of web activity at 1 week. Results: 85 reviews were randomised to each of the intervention and control arms. Google Analytics allowed 100% follow-up within 1 week of completion. Intervention and control reviews received a total of 1162 and 449 visits, respectively (IRR 2.7, 95% CI 2.2 to 3.3). Fewer intervention reviews had single page only visits (16% vs 31%, OR 0.41, 0.19 to 0.88) and users spent more time viewing intervention reviews (geometric mean 76 vs 31 s, ratio 2.5, 1.3 to 4.6). Other secondary metrics of web activity all showed strong evidence in favour of the intervention. Conclusions: Tweeting in this limited area of healthcare increases ‘product placement’ of evidence with the potential for that to influence care.